Das literarische Schaffen Manfred Winklers - Werkübersicht, Genese und Textpraktiken - Tempian, Monica (Naharaim, 2025)
Though awarded the Israeli Prime Minister's Prize for Hebrew Literature in 1999, the multifaceted Manfred Winkler (1922-2014), encompassing roles as a German and Hebrew poet, survivor-writer, translator, painter, and sculptor, has only recently garnered sustained scholarly attention. This delayed recognition can be attributed, in part, to Winkler's lifelong commitment to traversing geographical, national, ideological, and linguistic boundaries throughout his extensive career. It is only in the wake of a burgeoning interest in the life narratives of German-language refugees and immigrants to Israel, alongside their transcultural literary contributions, that the cultural and historical significance of Winkler's poetry has come to light. This article delves into Winkler's literary corpus and its inception, drawing upon the latest insights and research findings obtained through the author's archival and editorial work since 2014. It provides an overview of the predominant themes, writing practices, and tendencies within the works of this multilingual author and (self-)translator. Winkler, through his poignant portrayal of the traumas of war and the memories of the Holocaust and the Jewish-Arab conflict - with a sense of grief rather than from a position of judgment - delineates the fault lines and pivotal moments of nearly the entire 20th century.